La gestión municipal y su incidencia en el desarrollo de la atención al usuario de transporte público urbano luz del camino del cantón Buena Fe - Ube Toala, Roxanna Karina (2016)
This study analyzed the Municipal Management in Urban Public Transport Company "Light the Way" Canton Good Faith, implementing surveys and interviews with users, drivers and staff units, with the aim of analyzing the municipal management and its impact on the development of attention to urban public transport user. The importance of this work, the evaluation of the service provided by the monopoly company by drivers and officers shown. Speaking of servicing the customer service in the transport sector refers to the quality perceived by users. The quality of service is an important issue regarding the situation of comfort that they can feel the different users of a service. It determined that 100% of employees working in the carrier do not know that there is a manual of functions and procedures for each activity. Also in the field of municipal management by developing skills and managerial skills of local autonomous governments it will correspond exclusively to plan, regulate and control traffic, transport and road safety within their cantonal territory. Having assessed the impact of the lack of customer service it can be concluded that the company does not have a training plan that allows you to identify the attitude adjustments and human values that should be developed to provide a warm attention and fascinate its users. Finally a training plan for staff, drivers and officials of the carrier "Light the Way" was developed because users have always demanded the best deal and the best service to provide this service. Keywords. Municipal management, development, customer, user, transport.